IV.–A Note on Mr. Kahn's Paper - Hicks, J. R. (Review of Economic Studies, 1933)
IV.—A Note on Mr. Kahn's Paper Get access J. R. Hicks J. R. Hicks London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 1, October 1933, Pages 78–80, https://doi.org/10.2307/2967442 Published: 01 October 1933